ANALISIS PENERAPAN STANDAR SARANA PRASARANA DI SDN BEJI 01 KECAMATAN UNGARAN TIMUR - Tutik Yuliarsih; Dyah Ayu Permatasari; Farid Ubaidillah; Sudjono, Sudjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Educational facilities and infrastructure are very important components in supporting the optimal implementation of the educational process. According to Barnawi, educational facilities and infrastructure are